The relation between odontogenic inflammations and acceleration of erythrocyte sedimentation rate in patients with infectious endocarditis - Anna Janas; Adam Chiżyński; Monika Ratajek-Gruda; Piotr Osica (Kazimierz Wielki University, 2015)
Janas Anna, Chiżyński Adam, Ratajek-Gruda Monika, Osica Piotr. Relacja pomiędzy zębopochodnymi stanami zapalnymi a przyspieszonym odczynem Biernackiego u chorych z infekcyjnym zapaleniem wsierdzia = The relation between odontogenic inflammations and acceleration of erythrocyte sedimentation rate in patients with infectious endocarditis. Journal of Education, Health and Sport. 2015;5(2):109-116. ISSN 2391-8306. DOI: 10.5281/zenodo.15637 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A109-116 https://pbn.nauka.gov.pl/works/540839 http://dx.doi.org/10.5281/zenodo.15637 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 20.02.2015.   Relacja pomiędzy zębopochodnymi stanami zapalnymi a przyspieszonym odczynem Biernackiego u chorych z infekcyjnym zapaleniem wsierdzia   The relation between odontogenic inflammations and acceleration of erythrocyte sedimentation rate in patients with infectious endocarditis   Anna Janas1, Adam Chiżyński2, Monika Ratajek-Gruda2, Piotr Osica2   1 Zakład Stomatologii Ogólnej UM w Łodzi 2 Zakład Chirurgii Stomatologicznej UM w Łodzi     Adres do korespondencji: dr n. med. Piotr Osica Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251   Praca finansowana przez Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503/01   Streszczenie   Odczyn Biernackiego to wskaźnik sedymentacji erytrocytów. Jest miarą szybkości opadania krwinek czerwonych w osoczu krwi. Określany jest standardowo po upływie 1 godziny. Celem pracy było wykazanie relacji pomiędzy zębopochodnymi stanami zapalnymi a przyspieszonym OB. u chorych z infekcyjnym zapaleniem wsierdzia. Materiał i metody Roczną obserwacją kliniczną objęto 14 pacjentów, skierowanych na konsultację z infekcyjnym zapaleniem wsierdzia i przyspieszonym OB. U pacjentów badaniem klinicznym i radiologicznym stwierdzono zębopochodne stany zapalne, które usunięto chirurgicznie . Wyniki W badaniach kontrolnych po 1. i 3. miesiącach po zabiegu stwierdzono zmniejszenie wartości OB. z 2- cyfrowego na 1-cyfrowe. Wniosek Zębopochodne  stany zapalne powodują przyspieszone OB. u pacjentów z infekcyjnym zapaleniem wsierdzia.   Słowa kluczowe: zębopochodne stany zapalne, infekcyjne zapalenie wsierdzia.     Abstract   The erythrocyte sedimentation rate also called a sedimentation rate, is the rate at which red blood cells sediment in a period of one hour. The aim of the study was to show a relation between odontogenic infections and acceleration of erythrocyte sedimentation rate in patients with infectious endocarditis. Material and methods. Yearly observation of 14 patients, referred for a consultation because of infectious endocarditis and accelerated sedimentation rate. Clinical and radiological examination showed odontogenic inflammations, which were removed surgically. Results. Checkups after 1 and 3 months after the procedure showed a decrease in the sedimentation rate from two to one figure. Conclusion. Odontogenic inflammations cause acceleration of erythrocyte sedimentation rate in patients with infectious endocarditis.   Key words: odontogenic infections, infectious endocarditis.